THE BRIGHT PART OF PERSEUS ARM AND THE LENS - Shatsova, R. B.; Anisimova, G. B. (Одеські астрономічні публікації, 2011)
The part of Milky Way between l≈90° and 150°, related to the Perseus arm, stand out by its large brightness. It is due to the great number of supergiants, Cepheids, OB-associations, supernova, molecular clouds, γ-bursts, etc. The outlines of this part of the arm in the celestial projection almost coincide the Lens projection, formed by the intersecting radioloops’ shells II and III, well known by their synchrotron radiation. It means, that the bright Perseus arm part is observing through nearby to it Lens (r=100-250 pc). The arm parts, observing outside this Lens, are fainter for several magnitudes. The Sagittarius arm is observing through the Loop I. The modern data of the light absorption do not explain this phenomenon. This one and some other facts rise the hypothesis that the spur shells, in particular, the Lens are focusing, or in some other way make brighter passing through them radiation. It is important to estimate the role of the Lens effect in the existing picture of the spiral structure of the Galaxy, independently of the hypothesis.